2022
DOI: 10.1007/s00521-021-06776-z
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid metaheuristic approach using random forest and particle swarm optimization to study and evaluate backbreak in open-pit blasting

Abstract: Backbreak is a rock fracture problem that exceeds the limits of the last row of holes in an explosion operation. Excessive backbreak increases operational cost and also poses a threat to mine safety. In this regard, a new hybrid intelligence approach based on random forest (RF) and particle swarm optimization (PSO) are proposed for predicting backbreak with high accuracy to reduce the unsolicited phenomenon induced by backbreak in open-pit blasting. A data set of 234 samples with 6 input parameters including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…A powerful bagging-based ensemble algorithm is the distributed random forest (DRF), which improves learning by addressing the problem of local optima and covering the full search space [ 48 ]. It uses a combination of decision trees to maximize the model classification efficiency rather than using just one as a weak learner.…”
Section: Methodsmentioning
confidence: 99%
“…A powerful bagging-based ensemble algorithm is the distributed random forest (DRF), which improves learning by addressing the problem of local optima and covering the full search space [ 48 ]. It uses a combination of decision trees to maximize the model classification efficiency rather than using just one as a weak learner.…”
Section: Methodsmentioning
confidence: 99%
“…Each tree is made up of column variables and row observations that are chosen at random. A single DT is difficult to predict accurately, but all DTs form a forest, allowing the aggregated findings to incorporate the outcomes of all DTs, resulting in a more accurate overall prediction [59].…”
Section: Random Forest 351 Definitionmentioning
confidence: 99%
“…Dai Yong et al (2022) modeled BB based on the parameters of hole length (L), spacing (B, S), stemming (T), specific drilling (SD), specific charge (PF), and an output parameter (BB) using random forest (RF) and particle optimization swarm (PSO) algorithms. The results showed that parameters L and T have the highest Gini index in the RF model, indicating their effect on the output of the model (Dai et al, 2022). In 2021 and 2022, Sohrabi et al used Whale algorithm and neural network to optimize crude oil and coal price estimation.…”
Section: Introductionmentioning
confidence: 99%